Against Self‑Refexive Confessions: Collective Dialogues to Progressively Transform Academic North–South Collaborations - Mertens, Kewan; Cely, Adriana Moreno; Nyakato, Viola N. (The European Journal of Development Research, 2024)
This paper introduces an approach to transform academic North–South collaborations. Critiquing entrenched dynamics in inter-university collaborations, we propose a methodology for unlearning colonial modes of thinking and relating. The transformative dialogues proposed in this paper illustrate how researchers can jointly engage in generating collective refexivity and mutual accountability to challenge established norms in academia. Using autoethnographic vignettes, we demonstrate how these dialogues bring to the fore our complicities in reproducing North–South imbalances as well as the difculty of unsettling power dynamics and fostering collective co-existence across diferences. By nurturing a safe space for tuning in with each other, transformative dialogues turn self-refexivity into a relational and dialogical process. They help (1) to refect on our past and present experiences, (2) to perceive failure as a learning stimulus rather than defciency or shame, (3) to confront us with our complicity in reproducing neocolonial power dynamics in academic collaborations, and (4) to transform interpersonal dynamics within academic collaborations.
Keywords: Dialogical Refexivity; Decoloniality; North-South Collaborations; Autoethnography